2014
DOI: 10.1093/brain/awu022
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine transporter deficiency syndrome: phenotypic spectrum from infancy to adulthood

Abstract: Dopamine transporter deficiency syndrome is an SLC6A3-related progressive infantile-onset parkinsonism-dystonia that mimics cerebral palsy. Ng et al. describe clinical features and molecular findings in a new cohort of patients. They report infants with classical disease, as well as young adults manifesting as atypical juvenile-onset parkinsonism-dystonia, thereby expanding the disease spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
203
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 140 publications
(216 citation statements)
references
References 35 publications
(69 reference statements)
10
203
1
2
Order By: Relevance
“…DAT deficiency syndrome was recently described as an autosomal recessively inherited disease, manifesting in childhood, typically early infancy, with parkinsonism-dystonia (14,15,48). Mutations in SLC6A3 that probably lead to ER retention of the encoded DAT proteins were identified as the cause of disease.…”
Section: Discussionmentioning
confidence: 99%
“…DAT deficiency syndrome was recently described as an autosomal recessively inherited disease, manifesting in childhood, typically early infancy, with parkinsonism-dystonia (14,15,48). Mutations in SLC6A3 that probably lead to ER retention of the encoded DAT proteins were identified as the cause of disease.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the impact of DAT genetic variation on behavioral changes underlying mental illness stems from pioneering studies of the DAT knockout mouse, which demonstrated that genetic elimination of DAT expression reduces presynaptic DA stores, elevates extracellular DA, and produces hyperactivity in a novel environment (Giros et al, 1996). However, humans that are homozygous for loss-offunction DAT (SLC6A3) alleles present with a complex disorder that resembles PD, rather than ADHD (see section V.B; Kurian et al, 2011;Ng et al, 2014). Instead, clinical studies that genetically screen individuals with ADHD, as well as preclinical studies using cell lines and genetic mouse models, have suggested that variations in the genes encoding for DAT, rather than simple loss of function, and/or DA receptors are associated with risk for ADHD (Gill et al, 1997;Bobb et al, 2005;Mazei-Robison et al, 2005;Sakrikar et al, 2012;Mergy et al, 2014).…”
Section: Dopamine Transporter Vesicular Monoaminementioning
confidence: 99%
“…In addition, loss-of-function mutations of the human SLC6A3 gene that encodes DAT have been linked to infantile parkinsonism-dystonia (also known as DAT deficiency syndrome; Kurian et al, 2009Kurian et al, , 2011, which is a severe neurologic syndrome that usually presents in early infancy with hypokinetic parkinsonism (Assmann et al, 2004). Of note, recent studies have shown evidence that DAT missense mutations can also lead to later-onset DAT deficiency syndrome and parkinsonism in adolescents and adults (Hansen et al, 2014;Ng et al, 2014). Decreases in VMAT2 within the striatal brain regions as assessed by [ 11 C]dihydrotetrabenazine (DHTBZ) binding have also been reported in patients with PD (de la Fuente-Fernández et al, 2011).…”
Section: Dopamine Transporter Vesicular Monoaminementioning
confidence: 99%
“…Further to this point, humans bearing homozygous, loss-offunction DAT mutations as seen in the DAT KO model, present with a complex disorder that, in juvenile stages, resembles Parkinson's disease (40,41). These findings suggest that DAT contributions to disorders such as ADHD and BPD may derive from less severe or qualitatively distinct changes in DAT activity than simple loss of function.…”
mentioning
confidence: 95%